2021
DOI: 10.1016/j.jpha.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into conjugation of antitumor-active unsymmetrical bisacridine C-2028 with glutathione: Characteristics of non-enzymatic and glutathione S-transferase-mediated reactions

Abstract: Unsymmetrical bisacridines (UAs) are a novel potent class of antitumor-active therapeutics. A significant route of phase II drug metabolism is conjugation with glutathione (GSH), which can be non-enzymatic and/or catalyzed by GSH-dependent enzymes. The aim of this work was to investigate the GSH-mediated metabolic pathway of a representative UA, C-2028. GSH-supplemented incubations of C-2028 with rat, but not with human, liver cytosol led to the formation of a single GSH-related metabolite. Interestingly, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Last, GSH levels were minimally affected (at any time of exposure), suggesting prevention of GSH conjugation (Figure 5C). In addition, a reversible inhibitor of GST (ethacrynic acid) was utilized (Figure 5A) as previously described by others [35][36][37]. Finally, cells pre-treated for 4 h to 30 µM of ethacrynic acid, followed by exposure to PhEF extract (0.75-2.5% v/v) for another 0.5-48 h, provided optimized experimental conditions in the context of not being associated with the induction of any cytotoxicity (Figure S5A, Table S3).…”
Section: Kinetic Determination Of Peitc-nac Conjugate Formationmentioning
confidence: 99%
“…Last, GSH levels were minimally affected (at any time of exposure), suggesting prevention of GSH conjugation (Figure 5C). In addition, a reversible inhibitor of GST (ethacrynic acid) was utilized (Figure 5A) as previously described by others [35][36][37]. Finally, cells pre-treated for 4 h to 30 µM of ethacrynic acid, followed by exposure to PhEF extract (0.75-2.5% v/v) for another 0.5-48 h, provided optimized experimental conditions in the context of not being associated with the induction of any cytotoxicity (Figure S5A, Table S3).…”
Section: Kinetic Determination Of Peitc-nac Conjugate Formationmentioning
confidence: 99%
“…GAP can remove and detoxify carcinogens, but high expression of GAP may protect cancer cells by conferring resistance to some drugs [ 21 , 22 ]. Targeting GAP is a potential strategy to induce cancer cell death [ 22 , 23 ]. Therefore, monitoring the metabolite profiling of GAP is of great importance and contributes to research on drugs and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we showed that C-2028 was rapidly conjugated with glutathione (GSH) to only one main product (GSH S-conjugate) via the catalytic action of rat microsomal and cytosolic GSH S-transferases (GSTs) [8]. No kinetic data for this reaction have been assessed yet.…”
Section: Introductionmentioning
confidence: 99%